Assessment of effectiveness of selected adaptation actions to climate change. The example of the New Centre of Lodz. - Bochenek, Anna Dominika; Klemm, Katarzyna; Woźna, Magdalena (Budownictwo i Architektura / Civil and Architectural Engineering, 2022)
The increasing average annual temperature value is observed in many cities around the world. More and more often, not only the Southern Europe inhabitants, but also those from the Central and Northern Europe are exposed to thermal stress. Nature Based Solutions (NBS) play a key role in mitigation, i.e. the process of alleviating the negative effects of climate change in highly urbanized areas. The main objective of this study is to answer the question whether the planned spatial activities involving the use of NBS solutions in the New Centre of Lodz contribute to the improvement of the urban spaces’ microclimate and the thermal comfort of people in the external environment. The subject of the work is the microclimate of urban spaces, understood as a climatic conditions set, in particular thermal conditions, in a given, small area. The spatial scope of the work covers a 30-hectare part of the New Centre of Lodz limited by the following streets: Kilińskiego, Narutowicza, Piotrkowska, Tuwima, which is currently undergoing a large-area revitalization process. In order to determine the microclimate conditions and thermal comfort, numerical simulations conducted in the ENVI-met program were used.